STAT3 Genotypic Variant rs744166 and Increased Tyrosine Phosphorylation of STAT3 in IL-23 Responsive Innate Lymphoid Cells during Pathogenesis of Crohn’s Disease - Ying Tang; Sanda A. Tan; Atif Iqbal; Jian Li; Sarah C. Glover (Journal of Immunology Research)
Crohn’s disease (CD) results from dysregulated immune responses to gut microbiota in genetically susceptible individuals, affecting multiple areas of the gastrointestinal tract. Innate lymphoid cells (ILCs) are tissue-resident innate effector lymphocytes which play crucial roles in mucosal immune defense, tissue repair, and maintenance of homeostasis. The accumulation of IFN-γ-producing ILC1s and increased level of proinflammatory cytokines produced by ILCs has been observed in the inflamed terminal ileum of CD patients. To date, the precise mechanisms of ILC plasticity and gene regulatory pathways in ILCs remain unclear. Signal transducer and activator of transcription 3 (STAT3) regulates gene expression in a cell-specific, cytokine-dependent manner, involving multiple immune responses. This study proposes the positive correlation between the prevalence of STAT3 rs744166 risky allele “A” with the severity of disease in a cohort of 94 CD patients. In addition, the results suggest an increased STAT3 activity in the inflamed ileum of CD patients, compared to unaffected ileum sections. Notably, IL-23 triggers the differentiation of CD117+NKp44- ILC3s and induces the activation of STAT3 in both CD117+NKp44- and CD117-NKp44- ILC subsets, implying the involvement of STAT3 in the initiation of ILC plasticity. Moreover, carriage of STAT3 “A” risk allele exhibited a higher basal level of STAT3 tyrosine phosphorylation, and an increased IL-23 triggered the pSTAT3 level. We also demonstrated that there was no delayed dephosphorylation of STAT3 in ILCs of both A/A and G/G donors. Overall, the results of this study suggest that IL-23-induced activation of STAT3 in the CD117-NKp44- ILC1s involves in ILC1-to-ILC3 plasticity and a potential regulatory role of ILC1 function. Those genetically susceptible individuals carried STAT3 rs744166 risky allele appear to have higher basal and cytokine-stimulated activation of STAT3 signal, leading to prolonged inflammation and chronic relapse.